1992
DOI: 10.1111/j.1365-2389.1992.tb00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different models for phosphate sorption as a function of the iron and aluminium oxides of soils

Abstract: Phosphate sorption on topsoil and subsoil samples from different soils located in the eastern part of Germany was studied. Two models were fitted to sorption data obtained after 4 and 40 d of gentle shaking. The models differ with respect to the fractions of iron and aluminium (hydr)oxides that are considered and whether the phosphate initially sorbed in the soil is taken into zccount. Oxalate-extractable P, (Pox), appears to be a major part of the total soil P. The total P sorption measured, F, was predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
96
2
5

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 26 publications
10
96
2
5
Order By: Relevance
“…Decreasing soil pH also increases the positive charge around Al and Fe oxides and thereby increases anion adsorption (Muljadi et al 1966;Bowden et al 1980). Oxalate extractable Al and Fe ox levels measured at these sites were in the upper range of the values found in the literature (Shanley 1992;Freese et al 1992;Devau et al 2009;Kanˇa et al 2011) and are higher than levels expected for geologically young/recently deglaciated soils (Peltovuori et al 2002), although they are still much lower than those found in highly weathered soils such as Ultisols (e.g., 3000Á8000 mmol Al g (1 ; 500Á5000 mmol Fe g (1 ; Shaw 2001). Although Al exg and Fe ox were higher at the lower pH CaCl 2 study soils, there was a negative relationship between labile [P] and B-horizon soil pH CaCl 2 across the study sites (Fig.…”
Section: Patterns In Stream Total Phosphorussupporting
confidence: 51%
See 1 more Smart Citation
“…Decreasing soil pH also increases the positive charge around Al and Fe oxides and thereby increases anion adsorption (Muljadi et al 1966;Bowden et al 1980). Oxalate extractable Al and Fe ox levels measured at these sites were in the upper range of the values found in the literature (Shanley 1992;Freese et al 1992;Devau et al 2009;Kanˇa et al 2011) and are higher than levels expected for geologically young/recently deglaciated soils (Peltovuori et al 2002), although they are still much lower than those found in highly weathered soils such as Ultisols (e.g., 3000Á8000 mmol Al g (1 ; 500Á5000 mmol Fe g (1 ; Shaw 2001). Although Al exg and Fe ox were higher at the lower pH CaCl 2 study soils, there was a negative relationship between labile [P] and B-horizon soil pH CaCl 2 across the study sites (Fig.…”
Section: Patterns In Stream Total Phosphorussupporting
confidence: 51%
“…Both Al ox and Fe ox are important sorbents for phosphate and other anions (Freese et al 1992;Lookman et al 1995;Kanˇa and Kopa´cˇek 2006) and soils with high Al ox and Fe ox concentrations have a high capacity for P sorption (Yuan and Lavkulich 1994). Decreasing soil pH also increases the positive charge around Al and Fe oxides and thereby increases anion adsorption (Muljadi et al 1966;Bowden et al 1980).…”
Section: Patterns In Stream Total Phosphorusmentioning
confidence: 99%
“…Lower amounts of extracted P from more clayey soils were attributed to differential neutralization of the acid extracting solution as related to differences in soil surface area in contact with the M-III solution, or to re-adsorption of the extracted P (Kamprath and Watson 1980). Also, since clay minerals are not likely to occlude P compared with amorphous minerals, P sorbed onto clay minerals is a quantitatively important part of reversibly sorbed P (Freese et al 1992). Thus, according to this, (P/Al) M-III ratios could have been underestimated by the M-III procedure in fine-compared with coarse-textured soils.…”
Section: Critical (P/al) M-iii Ratios From P W Critical Value In the mentioning
confidence: 96%
“…For soils with initial low P content, F r is a good approximation of F m . However, in addition to F r determined under a given reaction time and concentration, the assessment of total P sorption capacity (F m ) should preferably include an estimate of the amount of P already sorbed when the initial P content of a soil is significant (Freese et al 1992). The initial P ox content of the soil may be used to account for the amount already sorbed (F m = F r + P ox ; Schoumans et al 1987;Van der Zee and Van Riemsdijk 1988;Freese et al 1992Freese et al , 1995.…”
mentioning
confidence: 99%